Global Civics : Responsibilities and Rights in an Interdependent World - Altınay, Hakan (Book collections on Project MUSE., 2011)
This thoughtful book debates civics in a universal context. It clearly illustrates that we cannot achieve the cooperation that is needed for a globalizing century without developing some form of "global civics."